Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5555076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5555076 10.53832/edtechhub.0051 2339240:7EJ6NEY6 2339240:T92LLPYZ 2339240:YKA7P6GC 2405685:CJ35EP8W 2405685:ELJ87ZBC 2405685:MHMXZI8J 2405685:MXVNKUM2 2405685:P22BR78B 2405685:UU5ZKKBE 2405685:X2ZWDMSU 2486141:F5MWP7EH 2534379:NKAFRXZM
Keywords: _r:AddedByZotZen

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5555076 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5555076 10.53832/edtechhub.0051 2339240:7EJ6NEY6 2339240:AD3D9NRM 2339240:T92LLPYZ 2339240:YKA7P6GC 2405685:CJ35EP8W 2405685:ELJ87ZBC 2405685:MHMXZI8J 2405685:MXVNKUM2 2405685:P22BR78B 2405685:SNBG3VHT 2405685:UU5ZKKBE 2405685:X2ZWDMSU 2486141:F5MWP7EH 2534379:NKAFRXZM
Keywords: _r:AddedByZotZen

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
ZenodoArchiveID: 5652063 previousDOI: 10.5281/zenodo.4430545 previousZenodoArchiveID: 4430545 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4430545 10.5281/zenodo.5652063 2339240:94IZR4ET 2339240:TST2YB8H 2405685:3BWKQDYQ 2405685:FEXGB4IJ 2405685:ZGYUEEZQ
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

Cost-Effectiveness and EdTech: Considerations and case studies - Chuang, Rachel; Burnett, Nicholas; Robinson, Elizabeth (EdTech Hub, 2021)
The answer to the question ‘What is cost-effective EdTech?’ is highly nuanced, as it depends on the choice of the initiative, its design, implementation, intended audience, and how the local context is addressed. We compiled select case studies that examine how EdTech was used in cost-effective and less cost-effective ways. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651978 previousDOI: 10.5281/zenodo.5213890 previousPreviousDOI: 10.5281/zenodo.4897985 previousPreviousDOI: 10.5281/zenodo.4897985 PreviousDOI: 10.5281/zenodo.4897985 PreviousDOI: 10.5281/zenodo.4897985 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.5213890 10.5281/zenodo.4897985 10.5281/zenodo.5213890 10.5281/zenodo.5651978 2339240:C93CUDGR 2339240:XJDIEYV8 2405685:DQX9SUB6 2405685:FZ937TYM 2405685:WEFTUGTJ 2405685:YU9RLZ98
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

The effectiveness of technology-supported personalised learning in low- and middle-income countries: A meta-analysis - Major, Louis; Francis, Gill A.; Tsapali, Maria (British Journal of Educational Technology, 2021)
Digital technology offers the potential to address educational challenges in resource-poor settings. This meta-analysis examines the impact of students' use of technology that personalises and adapts to learning level in low- and middle-income countries. Following a systematic search for research between 2007 and 2020, 16 randomised controlled trials were identified in five countries. Studies involved 53,029 learners aged 6–15 years. Coding examined learning domain (mathematics and literacy); personalisation level and delivery; technology use; and intervention duration and intensity. Overall, technology-supported personalised learning was found to have a statistically significant—if moderate—positive effect size of 0.18 on learning (p = 0.001). Meta-regression reveals how more personalised approaches which adapt or adjust to learners' level led to significantly greater impact (an effect size of 0.35) than those only linking to learners' interests or providing personalised feedback, support, and/or assessment. Avenues for future research include investigating cost implications, optimum programme length, and teachers' role in making personalised learning with technology effective. Practitioner notes What is already known about this topic? Promoting personalised learning is an established aim of educators. Using technology to support personalised learning in low- and middle-income countries (LMICs) could play an important role in ensuring more inclusive and equitable access to education, particularly in the aftermath of COVID-19. There is currently no rigorous overview of evidence on the effectiveness of using technology to enable personalised learning in LMICs. What this paper adds? The meta-analysis is the first to evaluate the effectiveness of technology-supported personalised learning in improving learning outcomes for school-aged children in LMICs. Technology-supported personalised learning has a statistically significant, positive effect on learning outcomes. Interventions are similarly effective for mathematics and literacy and whether or not teachers also have an active role in the personalisation. Personalised approaches that adapt or adjust to the learner led to significantly greater impact, although whether these warrant the additional investment likely necessary for implementation at scale needs to be investigated. Personalised technology implementation of moderate duration and intensity had similar positive effects to that of stronger duration and intensity, although further research is needed to confirm this. Implications for practice and/or policy: The inclusion of more adaptive personalisation features in technology-assisted learning environments can lead to greater learning gains. Personalised technology approaches featuring moderate personalisation may also yield learning rewards. While it is not known whether personalised technology can be scaled in a cost-effective and contextually appropriate way, there are indications that this is possible. The appropriateness of teachers integrating personalised approaches in their practice should be explored given ‘supplementary’ uses of personalised technology (ie, additional sessions involving technology outside of regular instruction) are common.
Archive: https://zenodo.org/record/4817787 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13116 10/gj6k5n 2339240:382K6GCA 2339240:53R3ZYT5 2339240:6HPRIAVP 2339240:7C7I9C4I 2339240:CYQPAERV 2339240:EXFAZMDQ 2339240:P2I2EU98 2339240:RM59PWFE 2405685:4MGG3JS3 2405685:5U948655 2405685:6UZHTZ8G 2405685:FIXCCB5I 2405685:HBGSTQ7X 2405685:QFTDGH3C 2405685:RZNJVMWH 2405685:V8UFGT52 2405685:WTT4UQ43 2405685:ZD4YGMMJ 4042040:G8KVDVSC
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted; computer-assisted learning; learning outcomes; low- and middle-income; meta-analysis; personalisation; personalised adaptive learning; ⛔ No DOI found

WhatsApp-Assisted Learning for Refugees. End of Sandbox Sprint 3 - Boujikian, Michèle; Carter, Alice; Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4783017 2405685:89DPN3SP 2405685:EVSZNGMA
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Integration of Technology in Education for Marginalised Children in an Urban Slum of Dhaka City During the Covid-19 Pandemic - Islam, Touhidul; Hussain, Maria; Shimul, Shafiun Nahin; Rupok, Rifat Islam; Orthy, S.R.Khan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5602863 10.53832/edtechhub.0063 2339240:I3JETHDB 2405685:5ZF9VGMK 2405685:6P5Q5IRZ 2405685:BIRTYTRC
Keywords: _r:AddedByZotZen

The Power of Girls' Reading Camps: Exploring the impact of radio lessons, peer learning and targeted paper-based resources on girls’ remote learning in Kenya - Amenya, Donvan; Fitzpatrick, Rachael; Njeri, M.E.; Naylor, Ruth; Page, Ella; Riggall, Anna (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651935 previousDOI: 10.5281/zenodo.4923094 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4923094 10.5281/zenodo.5651935 2339240:6ELB8P84 2339240:HZ3EBZ29 2405685:79JJ5T29 2405685:P8IAN448 2405685:RU8ET9S2
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Lack of Means or Lack of Awareness? Survey findings: barriers to learning with WhatsApp in refugee camps in Lebanon - Boujikian, Michèle; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4780972 2405685:4UQT8WRN 2405685:WWUQ7VRT
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5524840 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5524840 10.53832/edtechhub.0047 2339240:LSC89UVX 2339240:RIE9TWUK 2339240:SI398B6V 2405685:54BCQ23M 2405685:6NNCFPHE 2405685:77NJVUB6 2405685:HUY7VUM6 2405685:VTQDT65R 2405685:WFDCC7KZ 2534378:BQ8BJBGF
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

Methodology for literature reviews - Haßler, Björn; Adam, Taskeen; Allier-Gagneur, Zoe; Blower, Thomas; Brugha, Meaghan; Damani, Kalifa; Hennessy, Sara; Martin, Kevin; Megha-Bongnkar, Ghislaine; Murphy, Mary; Walker, Hannah; Walker, Hannah (EdTech Hub, 2021)
An output of the EdTEch Hub
previousPreviousDOI: 10.5281/zenodo.4557508 PreviousDOI: 10.5281/zenodo.4557508 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4557508 10.53832/edtechhub.0002 2129771:BKEP82PS 2339240:KF364I3I 2405685:2CKWI7RR 2405685:ESKCB3SZ 2405685:SRFG8S6C
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

EdTech Interventions for Deaf Learners: Sprint 2 Review - Rahman, Asad; Siddiqui, Maira; Shaikh, Sarah; Geary, Richard; Awasen, Aaron; Plaut, Daniel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4924787 10.53832/edtechhub.0131 2405685:D7JX8S7S
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Syṡtemic Mixed-Methods Research — a conceptual framework for scalable EdTech research - Haßler, Björn; El-Serafy, Yomna; Khalayleh, Abdullah; McBurnie, Chris (EdTech Hub, 2021)
previousPreviousDOI: 10.5281/zenodo.4557484 previousPreviousDOI: 10.5281/zenodo.4557484 previousPreviousDOI: 10.5281/zenodo.4557484 PreviousDOI: 10.5281/zenodo.4557484 KerkoCite.ItemAlsoKnownAs: 2129771:HT9D5C8E 2129771:HT9D5C8E 10.5281/zenodo.4557484 10.53832/edtechhub.0001 2129771:HT9D5C8E 2339240:HPLKGS4I 2339240:RQGHJZV7 2339240:S3YSSL2W 2405685:K2FX6IVZ 2405685:T6YJ3L5G 2405685:TD2ASC4G 2405685:ZNQCJ5R7
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Investigating the Impact on Learning Outcomes Through the Use of EdTech During Covid-19: Evidence from an RCT in the Punjab province of Pakistan - Adil, Fareeha; Nazir, Rabia; Akhtar, Misbah (EdTech Hub, 2021)
The objective of the current study is to test the impact of low-tech solutions on maths, Urdu, and English scores for students in the underdeveloped district of Bahawalnagar, which is situated in the southern part of Punjab in Pakistan. The target population for this study is Grade 8 students attending private schools. We have tested the impact of three interventions, namely: Teaching at the right level (TaRL), Fortnightly assessments (FAS) Digital teacher training sessions (DTS) Our findings show a significant and positive ‘Intention to Treat’ (ITT) impact on Urdu and English scores of the students in the TaRL treatment group. The students increased their English and Urdu scores by 0.56 SD. However, we found no significant impact of the intervention on maths scores in the TaRL treatment group. Fortnightly assessments and digital teacher training sessions were also found to contribute to higher English scores of the students. However, we found no ITT impact on the maths and Urdu scores for these treatment groups. The Local Average Treatment Effect (LATE) analysis revealed positive and significant improvement in Urdu and English scores of the students in the TaRL treatment group. Key stakeholders whom we interviewed suggested that redesigning the curriculum and incorporating TaRL within this approach could facilitate enhancement in learning outcomes in students in deprived areas. Our findings are important to help inform policymakers on the importance of designing and implementing cost-effective, low-tech solutions to help reduce learning gaps. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5654887 10.53832/edtechhub.0067 2339240:VNTPMCJQ 2339240:XLHSGBDA 2405685:FSVST5BF 2405685:HVDCZZVG 2405685:L5WPA5SN 2405685:YWENAQDF
Keywords: _r:AddedByZotZen

Lessons learnt from education data mapping in Africa: Workshop summary and synthesis - Pambe, Rigobert; Kadzamira, Esme; Mjomba, Renaldah; Lawson, Laté; Onsomu, Eldah; Adam, Taskeen; Heady, Lucy; Mugo, John; Tinto, Teg-WendeIdriss (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5576416 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5576416 10.53832/edtechhub.0052 2339240:282R466B 2339240:EQWZQPHA 2405685:2B2RMIDY 2405685:AEQDZV3T 2405685:DX6WMTLN 2405685:NNN9EZ7J
Keywords: _r:AddedByZotZen

T-TEL Covid-19 Impact Assessment Study - Ananga, Eric; Kadiri, Abdul-Karim; Kporwodu, Marie; Nkrumah, Yahya; Whajah, Francis; Tackie, Majorie (2021)
ZenodoArchiveID: 4895400 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4895400 2339240:F8IYBAPY 2405685:57DYPNLR 2405685:DR6BDMJS 2405685:PTC9PGZW
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted

Community Help for Inclusive Learning and Development (CHILD): A Study of How Mobile Phones Were Used to Recruit and Equip Community Volunteers to Support Children’s Learning During Covid-19 School Closures in Zimbabwe - Power, Tom; Buckler, Alison; Ebubedike, Margaret; Tengenesha, Martha; Jama, Mbuso; Ndlovu, America; Mukoyi, Jane; Ndou, Mashudu; Mubaira, Simbarashe (EdTech Hub, 2021)
ZenodoArchiveID: 4557015 PrevoousDOI: 10.5281/zenodo.4502122 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4502122 10.5281/zenodo.4557015 2339240:6Z8Q4VYT 2339240:KCTXJNS6 2405685:HZRHPNI5
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Learning with technology during emergencies: A systematic review of K-12 education - Crompton, Helen; Burke, Diane; Jordan, Katy; Wilson, Samuel W. G. (British Journal of Educational Technology, 2021)
Emergency situations that cause damage to educational buildings or require the closure of schools due to unsafe health, environmental, or political conditions can be an unwelcomed interruption to education. Indeed, the recent COVID-19 pandemic created the largest disruption of education in history, affecting 94% of the world's student population. In emergencies, technology is often utilised as part of a crisis response protocol by continuing education using emergency remote education (ERE). The purpose of this study is to determine how technology has been used to continue K-12 learning remotely during an emergency. This systematic review included an aggregated and configurative synthesis to examine extant empirical work over eleven years, from January 2010 to December 2020. Following a rigorous, PRISMA selection process, 60 articles were included in the final analysis from 48 countries. Grounded coding of the strategies used for learning revealed the following categories: communication, delivery systems, student ERE readiness, partnerships, promoting student learning and engagement, and resources. Grounded coding of the technologies revealed that types of technologies used were divided into two major categories: Internet-based and non-Internet based, with the majority using Internet-based technologies. Practitioner notes What is already known about this topic The COVID-19 pandemic has caused school closures across the globe and prevented in-person school teaching. The rapid shift to distance education in schools can be conceptualised as ‘emergency remote education’ (ERE). Prior ERE research focused on bounded geographic locations where localised emergencies occurred. What this paper adds This provides the scholarly community with a unique systematic review of existing academic research on K-12 ERE implementation in emergencies. This provides aggregated data and analysis on the past 11 years of the types of emergencies, participants, subject domain, technologies used, and location information. This provides findings of the types of remote teaching strategies involving technology used to continue K-12 learning in emergency situations. This provides a set of recommendations on ERE for teachers, school leaders, policy makers, and funders. This provides researchers with a review of the field with identification of gaps and future research opportunities. Implications for practice and/or policy Recommendations regarding ERE are provided in this paper that will be of benefit to K-12 teachers, school leaders policymakers, and funders in the continuing COVID-19 pandemic and future emergencies. The research gaps highlighted in this paper, such as the lack of studies conducted in low and low middle-income countries, are presented with suggestions for much needed future research. This can lead to changes in practice and policy.
ZenodoArchiveID: 5652042 _eprint: https://bera-journals.onlinelibrary.wiley.com/doi/pdf/10.1111/bjet.13114 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13114 10.5281/zenodo.5652042 2339240:ELI3E5RF 2339240:TJNJX997 2405685:3KJJW6XZ 2405685:9V69ZAFP 2405685:BDG6N6PJ 2405685:JE8I8566 2405685:YY7LXWQB
Keywords: COVID-19; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _yl:b; _zenodo:submitted; disasters; emergencies; emergency remote education; pandemic

Understanding Barriers to Girls’ Access and Use of EdTech in Kenya During Covid-19 - Tembey, Lara; Baier, Jasmin; Ogolla, Concilia; Mohan, Prithika (EdTech Hub and Busara Center for Behavioural Economics, 2021)
The Covid-19 pandemic resulted in the closure of approximately 90,000 schools across Kenya, causing over 18 million pre-primary, primary, and secondary school learners to be out of school throughout 2020. These lockdown measures of Covid-19 are expected to amplify gender inequalities in education and girls’ access to school, with girls likely to have experienced losses in learning during the pandemic to a greater extent than their male counterparts (⇡Malala Fund, 2020). To enable continued learning during this period, numerous education technology (EdTech) solutions and products have been developed to enable remote learning. This technology can be a powerful tool for girls. Studies have shown that girls engage more than boys when provided with the same level of access to technology, and receive more benefits beyond the realm of formal education such as an increase in access to economic opportunities and a greater ability to make informed decisions about their own health (⇡Webb et al., 2020). However, social inequalities, norms and technological constraints can disproportionately prevent girls from accessing and benefiting from EdTech (⇡Crompton et al., 2021). As such, EdTech interventions and products need to be designed and implemented prioritising gender considerations, otherwise they risk increasing the digital gender divide both in terms of access and use of digital technologies and the internet and the development of skills needed to use digital technologies (⇡Kuroda et al., 2019). Our qualitative and quantitative research looked at how access and usage of learning content and edutainment through smartphone and low-tech (such as radio, Interactive Voice Response, TV) EdTech solutions can be optimised to ensure inclusivity of girls, in particular, focusing on the caregiver as the gatekeeper for access to EdTech resources. In terms of access, our research found that caregivers are primarily concerned about financial resources, books and tutors, and often do not consider using EdTech to access educational resources when they are looking for support for their children. Further, our research showed that digital literacy, caregiver involvement, norms about technology for education, and intention are the most promising levers to improve access and use of educational material. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5524805 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5524805 10.53832/edtechhub.0048 2339240:5D6SMESW 2339240:7NDUJC6J 2339240:M8IZH5DT 2339240:SIZUDNKL 2339240:XAXIKZJX 2339240:YPDDA6JD 2405685:45G9SKWR 2405685:5ENZ6TFU 2405685:EJ4PXU4S 2405685:JZM7W6QE 2405685:LCHJ5D5W 2405685:RUAJ8C8M
Keywords: _r:AddedByZotZen

A Work Plan for Content Creation - Groeneveld, Caspar; Kibga, Elia; Proctor, Jamie; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4617798 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4617798 2339240:V3PGSF2W 2405685:EH6F8M5P
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

A Monitoring and Evaluation Framework for Blended Learning: Pakistan Ministry of Federal Education and Professional Training - Khalayleh, Abdullah; Baloch, Imdad; Dele-Ajayi, Opeyemi; Kaye, Tom (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4633326 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4633326 2339240:DNCQ88UV 2339240:ILPGZU8E 2339240:SGQPIKMM 2405685:AR7EAIDU 2405685:XBPZPS3P 2405685:YP4V829F 2405685:ZL7H9N8P
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v3; _r:AddedByZotZen; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

A Theory of Change for a Technology-Enhanced Education System in Bangladesh - Clark-Wilson, Alison; Bashir, Amreen; Kaye, Tom (EdTech Hub, 2021)
The first of a trilogy of Theories of Change (TOCs) that focuses on learners as the main beneficiaries of an increasingly technology-enhanced education system in Bangladesh. Initially created with stakeholders to support the monitoring and evaluation of programmes designed to offer distance learning during the 2020 Covid-19 school closures, the TOC describes how access to educational activities of different modalities (TV, Radio, Smartphone, online platforms etc.) should lead to improved educational outcomes for learners in Classes 1-12. Keywords: Bangladesh; Theory of Change; technology-enhanced learning; education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5652015 KerkoCite.ItemAlsoKnownAs: 10.5281/edtechhub.0044 10.5281/zenodo.4610089 10.53832/edtechhub.0044 2339240:D4Q4RX94 2339240:YKVDDCEI 2405685:2T7DPIBU 2405685:BUHD2X9T 2405685:E4I95IWF 2405685:NP95DHA2 2405685:Q2MS5ZSE 2405685:ZSEHKGUN
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

EdTech and Covid-19: 10 Things to Know - Nicolai, Susan; Wilson, Samuel; Jefferies, Kate (EdTech Hub, 2021)
EDTECH AND COVID-19 10 THINGS TO KNOW Covid-19 has reshaped our world. In education, mass school closures have accelerated the global use of education technologies. Yet the benefits do not reach everyone. Since the start of the pandemic, EdTech Hub and its partners have been researching and applying evidence on what works in technology for education in different contexts. Here…
ZenodoArchiveID: 5651983 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5651983 2339240:C67KNIJR 2339240:IH4ZG3U7 2339240:JUZ57X4A 2339240:R39DB2EG 2339240:W7FD9YT3 2405685:26VNTFQU 2405685:94AITL9D 2405685:DQ5URLSY 2405685:GT33JADA 2405685:VJ488Z7L zotzenLib.CopiedFrom: 2339240:C67KNIJR
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

تكنولوجيا التعليم وجائحة كوفيد 19 - .10 أشياء يجب معرفتها - EdTech Hub Team (2021)
ZenodoArchiveID: 4709700 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4709700 2339240:IH4ZG3U7 2339240:JUZ57X4A 2339240:R39DB2EG 2405685:26VNTFQU 2405685:DQ5URLSY 2405685:VJ488Z7L
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Advancing Data-Driven Decision-Making for School Improvement: Findings from the One Tablet Per School User Testing Programme in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman; Waistell, Daniel; Nallo, Michael (MBSSE, EdTech Hub, Leh Wi Lan, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4896502 10.53832/edtechhub.0066 2339240:9A7P2GEI 2339240:PA2CB3JF 2339240:Q3RLYCNW 2339240:TMHE9JIR 2405685:2CEZ2LKN 2405685:9B56X45X 2405685:FAJLNB8S 2405685:KFTXK9K2 2405685:MPRD5RKR 2405685:PGUR927P 2405685:UKHA4WKY 2486141:A5SQMX8T 4656463:XTGYWNYB
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Let's Read — How Tusome Leveraged EdTech to Improve National Learning Outcomes. Governing Digital Transformation: Improving Outcomes in Education Systems - Myers, Christina; Kaye, Tom; Khalayleh, Abdullah (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4699337 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4699337 2339240:MQFC486E 2339240:YAXCDGIK 2405685:3GQXS67C 2405685:Q9F2PISN
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Learning from Experience: A post-Covid-19 data architecture for a resilient education data ecosystem in Sierra Leone - Fab Inc. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
2339240:7FA4YDWJ 2339240:YBKKN8XE KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.5498054 10.5281/zenodo.5498054 2339240:3H4M8YJ8 2339240:5S4BZY48 2339240:SRWI5WQJ 2405685:BCFK4Q23 2405685:JR65CZU2 2405685:JTKTA5X5 2405685:VQ3F9NQ7 2405685:ZLATZSGU 4656463:RIFY2UNL
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Les Technologies De L’enseignement Et Le Covid-19 - 10 Choses À Savoir - EdTech Hub Team (2021)
ZenodoArchiveID: 4709702 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4709702 2339240:IH4ZG3U7 2339240:JUZ57X4A 2339240:R39DB2EG 2405685:26VNTFQU 2405685:DQ5URLSY 2405685:VJ488Z7L
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

A Political Economy Analysis Framework for EdTech Evidence Uptake - Pellini, Arnaldo; Nicolai, Susan; Magee, Arran; Sharp, Sam; Wilson, Sam (EdTech Hub, 2021)
ZenodoArchiveID: 4540204 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4540204 10.5281/zenodo.4540204 2339240:26GYDUTU 2339240:2Q9AWGM3 2339240:IQ36IBT8 2339240:MDUWMNQ5 2339240:P9XQBBQC 2405685:856UY54Y 2405685:CZZ5WHT7 2405685:P9T68ACJ 2405685:UGZDH4LB
Keywords: _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Low-Tech Devices and Connectivity for Learning in Lebanon - Chuang, Rachel; Khalayleh, Abdullah (EdTech Hub, 2021)
This document was produced in response to a request from the FCDO Lebanon team for guidance on leveraging low-tech devices and enabling connectivity to support learners in Lebanon, aligning with school reopenings. The document compiles effective initiatives across Lebanon and other countries.
ZenodoArchiveID: 4140412 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4140412 2129771:9X3BTTLU 2339240:9PYYNK6J 2405685:ISTFVCA7 2405685:NS927T5K
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Using EdTech to Support Learning Remotely in the Early Years. Rapid Literature Review of Evidence from the Global Response to Covid-19. - Korin, Astrid (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org This topic brief examines the literature on technology-based, remote approaches to supporting learning in the early years for children from birth to age five, identifying promising practices for using EdTech in early childhood education (ECE) in low- and middle-income countries (LMICs). It draws on the nurturing care framework, Principles for Digital Development, and effective pedagogical practices for ECE.
ZenodoArchiveID: 4746391 previousDOI: 10.5281/zenodo.4746391 previousDOI: 10.5281/zenodo.4664510 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4664510 10.5281/zenodo.4746391 2339240:CJNJNHNU 2405685:RTQ64R3P 2405685:TD3Y79BH
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

Voices and Evidence from End-Users of the GLTV and GLRRP Remote Learning Programme in Ghana: Insights for inclusive policy and programming - Hodor, Raymond; Owusu, Ernest Adu; Ofori-Davis, Lucy; Afram, Alexander; Sefa-Nyarko, Clement (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5611467 10.53832/edtechhub.0064 2339240:E542Q29N 2405685:2A5NQEV8 2405685:6JC7RU69 2405685:T3ZQ74QF
Keywords: _r:AddedByZotZen

Mango Tree Literacy Labs’ Radio Programme Sandbox - Esbeck, Craig; Oloa, Charles; Brown, Victoria; Plaut, Daniel; Salami, Taiye (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4747475 2405685:RIPJWUDB
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted

A Literature Overview of Accountability and EdTech: Recommendations for Using Technology to Improve Accountability in Educational Systems from Ghana and Other LMICs. - McIntyre, Nora; Sabates, Ricardo; Eberhardt, Molly Jamieson (EdTech Hub, 2021)
ZenodoArchiveID: 4575561 PreviousDOI: 10.5281/zenodo.4468852 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4575561 2339240:DTA9GETP 2339240:V8PHTCMI 2405685:5TQ3YM2R 2405685:AI9EYM2F 2405685:E5W5QCIE
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

A Country-Level Research Review: EdTech in Tanzania - Jordan, Katy; Proctor, Jamie; Koomar, Saalim; Bapna, Akanksha (Zenodo, 2021)
This document presents a review of the research landscape in Tanzania in relation to EdTech research focused on learners, teachers, or systems at the level of school-based education, excluding higher education (HE). The review draws upon the research literature, policy documents, grey literature, and interviews with key stakeholders in order to present an overview of the research landscape in Tanzania. There is a substantial body of relevant EdTech research which has been undertaken in Tanzania in the past decade. Eighty research articles were identified for inclusion in the review. This document provides an overview of trends in this literature and key actors and projects, and provides a specific focus upon existing research which relates to EdTech Hub’s ‘high-potential evidence gaps’ (HPEG) framework. In combination with political economy analysis, three areas for future research which would be practical and likely to have high impact are identified and described.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4618376 10.5281/zenodo.5652060 2339240:F8ER2X27 2339240:KZ7L8K2X 2339240:YKGMJASP 2405685:3F4ASVFA 2405685:IA77HHMV 2405685:RQGJRKVS 2405685:TYZ4Y65R 2405685:VRE5DB5K
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodoETH

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
ZenodoArchiveID: 4332693 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4332693 2339240:2FHWWFA3 2339240:322MPSF7 2339240:8BXMXD7P 2339240:BTJ8QHAD 2339240:BTPX7CIX 2339240:DZSHD5WZ 2339240:EEUENHU3 2339240:HSFA8Z7Q 2339240:M3YUXFYS 2339240:Q2I8K6L8 2339240:SILWX2ZS 2339240:WEEFFITS 2339240:XHVAUXYZ 2405685:347U73VH 2405685:4LA8N3BT 2405685:8F46F44X 2405685:94F2MYRK 2405685:BHLDEAHG 2405685:CQXKYRLY 2405685:CSJHU24F 2405685:DYB6V7DK 2405685:EIQD4I2E 2405685:GUHMK274 2405685:HXF4GM6M 2405685:PBXBB7LF 2405685:QVG25MBV 2405685:R2YGTN82 2405685:R7Q7CT4P 2405685:SNZ55MKE 2534378:42JICVEU
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo; Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Eight Reasons Why EdTech Doesn’t Scale: How sandboxes are designed to counter the issue - Simpson, Lea; Carter, Alice; Rahman, Asad; Plaut, Daniel (EdTech Hub, 2021)
The EdTech Hub’s sandbox approach offers implementers and decision makers a clear way to implement and scale only the most effective EdTech interventions. In this position paper we share our view on why EdTech isn’t scaling and how we see the sandboxes approach addressing them. Keywords: innovation; implementation; sandboxes; EdTech; scale; experimentation An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4966322 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4966322 10.53832/edtechhub.0115 10.53832/edtechhub.0116 2405685:8HKCSIRC
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

The Sandbox Handbook v1.0: A guide to growing and testing EdTech ideas - Rahman, Asad; Carter, Alice; Plaut, Daniel; Dixon, Dixon; Salami, Taiye; Schmitt, Laurel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5120788 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5120788 10.5281/zenodo.5142473 2405685:3C8VWLJP 2405685:772S7Z4R 2405685:CW2FHVT8
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodo:submitted

Inequalities in Girls’ Learning Opportunities via EdTech: Addressing the Challenge of Covid-19 - Crompton, Helen; Chigona, Agnes; Jordan, Katy, Jordan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.4917252 10.5281/zenodo.4917252 2339240:G2X4SJI9 2339240:MUSPGK9F 2339240:MVU3QIHM 2339240:NQF22P32 2405685:B2ABXUCR 2405685:D6PWMC4I 2405685:HW7NU96L 2405685:JWIHBL5M 2405685:PXBXCZ29 2405685:YHC5ZPU8
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen

Keep Kenya Learning: Helping Caregivers Support Learning at Home Sprint 1 - Mbatha, FaithMbithe; Crook, Rebecca; Plaut, Daniel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org Our research indicates that guidance and resources are necessary but insufficient in equipping caregivers to support their children’s learning. In Sprint 1, caregiver confidence and community emerged as important enablers of home learning. In our interviews, caregivers communicated how they felt limited by their lack of or outdated education. Global interventions indicate that reinforcing a sense of community for caregivers and enabling them to learn from modelling by trusted messengers are pathways to building greater engagement. Caregivers in both rural and urban communities expressed a willingness to engage with SMS (short message service) and online educational resources. However, it is clear that resource design must be: Accessible and understandable Credible and trusted Relevant and actionable.
ZenodoArchiveID: 4928926 PreviousDOI: 10.5281/zenodo.4747301 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4928926 2339240:PXT8SGSZ 2405685:9P9W4I53 2405685:A2D9FVTA 2405685:C2579UKC
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen; _zenodo:submitted; ⛔ No INSPIRE recid found

Development of a mobile app to improve numeracy skills of children with autism spectrum disorder: Participatory design and usability study - Ntalindwa, Theoneste; Nduwingoma, Mathias; Karangwa, Evariste; Rashid Soron, Tanjir; Uworwabayeho, Alphonse; Uwineza, Annette (JMIR Pediatr Parent, 2021)
Background: The use of information and communication technologies is transforming the lives of millions of people including children with autism spectrum disorder (ASD). However, the process of developing a user-friendly and effective mobile app needs to follow a complex standard protocol and culture-sensitive customization, and involves multiple sectors. This complex work becomes even more challenging when considering children with ASD in low- and middle-income countries as the users. Objective: This study aimed to design and develop a more intuitive mobile app to improve numeracy skills of children with ASD in Rwanda and evaluate the usability of the app. Methods: A participatory design approach was utilized in this study in which 40 children with ASD, 5 teachers, and 10 parents of children with ASD participated in focus group discussions (FGDs) and usability testing. A narrative literature review was performed to explore existing mobile apps and compare previous studies to design the questions for FGD and facilitate a framework for designing the app. The agile methodology was used to develop the mobile app, and the heuristics evaluation method was used to test and evaluate the usability of the initial version of the app to improve its functionalities. The interviews were recorded, transcribed, and analyzed following the guidelines of the qualitative narrative analysis (QNA) method. Results: During the FGDs the respondents shared their need for a mobile app in teaching and learning numeracy for children with ASD and pointed to possibilities of integrating the mobile app into existing curriculum. Ten themes emerged from the FGDs and exercise of developing the mobile app. The themes were related to (1) teaching and learning numeracy for children with ASD, (2) planning and development of a mobile app for a person with ASD, (3) testing a mobile app, (4) strength of the developed app against the existing ones, (5) behavioral maintenance and relapse prevention, (6) possibilities to integrate the mobile app into the existing curriculum, (7) data protection for users, (8) social implications, (9) challenges in Rwanda, and (10) focus on future. Conclusions: The community plays an important role in the planning, development, and evaluation of a mobile app for children with ASD. In this study, inputs from teachers and parents resulted in an optimally designed mobile app that can improve numeracy skills in children diagnosed with ASD to support the implementation of competency-based curriculum in Rwanda.
KerkoCite.ItemAlsoKnownAs: 10.2196/21471 2339240:BBJFJG68 2405685:QYR6FYRS
Keywords: autism spectrum disorder; education; information and communication technologies; learning; mathematics; mobile app; numeracy

Covid-19 and EdTech in Africa: A Country-Level Review Based on eLearning Africa Data - Damani, Kalifa (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 4703718 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4703718 2405685:CDC2W7Q6 2405685:HVQVC8TU
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _r:AddedByZotZen; _zenodo:submitted; _zenodoETH

An overview of 25 years of research on digital personalised learning in primary and secondary education: A systematic review of conceptual and methodological trends - Van Schoors, Rani; Elen, Jan; Raes, Annelies; Depaepe, Fien (British Journal of Educational Technology, 2021)
Due to the increasing digitisation, interest in digital personalised learning (DPL) continues to grow. Many empirical studies on the effect of adaptive tools have used a wide variety of conceptualisations and operationalisations of DPL. This systematic review aims to address the lack of consensus by presenting an analysis of empirical studies on technology for DPL in primary and secondary education. The work is guided by the following questions: (1) What are some different conceptualisations used in DPL research? (2) What types of tools are used in the studies and how are they implemented? (3) What is the current evidence on the impact of DPL with regard to student outcomes considering the nature of the current studies? A Boolean search string was used in the databases Web of Science and ERIC, resulting in a dataset containing 6,908 papers. A screening based on specific inclusion and exclusion criteria yielded 53 papers. Our findings revealed a great diversity in DPL conceptualisations, with several authors not defining the concept and others providing information regarding different elements such as technology, personalisation, personalisation target, personalisation source, personalisation method and personalisation outcomes. In line with these differences in conceptualisation of DPL, several DPL tools were used across the studies. Concerning the impact of DPL, a positive trend was observed on learning outcomes, although methodological differences need to be considered. The review ends with guidelines for future research. Practitioner notes What is already known There are many definitions and terms concerning DPL, resulting in a lack of consensus in conceptualisation. There is a wide variety of DPL tools with different adaptive dimensions. Many authors emphasise the benefits of DPL in educational practice including a possible impact on learning gains. What this paper adds Contribution to a thorough understanding of the conceptualisation of DPL. Insights into the diversity in DPL tools building on a framework of adaptivity by Vandewaetere and Clarebout (2014) and adds focus on tool implementation as a context element. Insight into the impact of DPL taking into account study design and outcome indicators. Implications for practice and/or policy An overview of the affordances of DPL to educational researchers, educational policy makers, and teachers is provided that can encourage them to think about its opportunities for everyday practice. Concrete suggestions for future research are discussed.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/bjet.13148 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13148 2339240:YZ9DIDAF 2405685:UARVNXGN
Keywords: adaptive learning; adaptive technology; digital personalised learning; educational technology; systematic review

EdTech and Covid-19: Insights from our Sandbox Portfolio. In Collaboration with Sandbox Partner Organisations - Rahman, Asad; Plaut, Daniel; Salami, Taiye; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4776960 2339240:JASYN9AV 2339240:URJVJP9H 2405685:7QBDH9I4 2405685:MXMPWAA2
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

EdTech to Reach the Most Marginalised: A Call to Action - Zubairi, Asma; Kreimeia, Adam; Jefferies, Kate; Nicolai, Susan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5495857 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5495857 10.53832/edtechhub.0045 2339240:23D7YNSM 2339240:ESWRJBRS 2339240:PVDW8BXZ 2405685:69W2G8TJ 2405685:6KFAB5ML 2405685:UYDUMKBR 2405685:V9Y8MUDX 2405685:W8DB96IE
Keywords: _DOILIVE; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

Country-Level Research Review: EdTech in Kenya - Myers, Christina; Kaye, Tom; Bapna, Akanksha; Williams, Ayesha; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5256847 2405685:FQP8MJIY 2405685:SNBW6BK6
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Country-Level Research Review: EdTech in Ghana - Tsapali, Maria; Major, Louis; Damani, Kalifa; Mitchell, Joel; Taddese, Abeba (EdTech Hub, 2021)
ZenodoArchiveID: 4613150 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4613150 2339240:7RV99GRF 2339240:KNG7CIPW 2405685:BHZPG5ZX 2405685:HH8PFJJE 2405685:IG4J94RS 2405685:YMAME8E6
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Global emergency remote education in secondary schools during the COVID-19 pandemic: A systematic review - Bond, Melissa; Bergdahl, Nina; Mendizabal-Espinosa, Rosa; Kneale, Dylan; Bolan, Faye; Hull, Poppy; Ramadani, Fjolla (International Public Policy Observatory, 2021)
The worldwide shift to emergency remote education in 2020 as a result of the COVID-19 pandemic impacted billions of students and teachers. A range of teaching and learning strategies were employed by schools as a result, despite confusing and sometimes contradictory government guidance, with systemic issues such as equity and access impacting heavily on disadvantaged students. In light of the findings of a recent IPPO evidence snapshot and roundtable event, and in order to gain further insight into how emergency remote education was experienced by secondary school students, parents and educators, a systematic review was conducted that collates and synthesises primary empirical studies across five key research questions focusing on student engagement, online assessment, peer collaboration, parent engagement, and future directions for online learning. Studies were searched for in May 2021 using Web of Science, Scopus, ERIC, Microsoft Academic Graph, ResearchGate and the COVID-19 living map, and were included if they focused on teaching and learning using blended or online approaches in secondary schools during the pandemic, that were published in English. Following quality assessment on scope and methodological rigour, 81 studies were included for narrative synthesis. The research studies were conducted in 38 countries, with 37% of studies from low or lower-middle income countries, and 63% from upper-middle income or high-income countries. Most of the evidence came from students (64%), followed by teachers (53%), with very few studies exploring the perceptions and experiences of parents (6%) or school leaders (5%). Findings reveal that self-regulation and understanding were the most frequently reported indicators of student engagement, with online assessment tools, learning management systems with collaborative tools, live synchronous lessons with peer and teacher interaction, and teacher-made videos considered particularly engaging. Social isolation was the most frequently reported indicator of disengagement, characterised by poor attendance in live lessons, a lack of opportunities to seek help with challenges and difficulties facilitating peer collaboration. Although many articles reported that assessment online was particularly challenging, 21 different types of online assessments strategies were identified, with online quizzes and formative online feedback the most frequently used. Live marking or recorded feedback and assessment were found to be particularly beneficial, as providing feedback during live lessons was sometimes challenging. Peer collaboration was facilitated through peer assessment, inquiry-based group work and experiments, aided by the use of collaborative software and combining multiple applications. Parental involvement and support contributed to student learning, although issues of equity impacted the extent to which they could engage with their children's learning, alongside gaps in family content knowledge and technological skills. Numerous implications for future policy relating to online and blended learning are provided.
KerkoCite.ItemAlsoKnownAs: 2339240:2E8EYFJA 2405685:JNJ5HLG9

EdTech evidence for Covid-19 response: Rapid evidence reviews of EdTech use in low-income and crisis contexts - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5512134 2405685:8M6GXINE 2405685:JGTWVQI4
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Country-Level Research Review: EdTech in Bangladesh - Zubairi, Asma; Kreimeia, Adam; Kaye, Tom; Ashlee, Amy (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 5651981 previousDOI: 10.5281/zenodo.5109678 previousDOI: 10.5281/zenodo.4943272 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4943272 10.5281/zenodo.5109678 10.5281/zenodo.5651981 2339240:TCHKGQZS 2405685:QUJHNPRD 2405685:XH44AG5R 2405685:YULPZE4D
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

The use of 'building blocks' to develop digital platforms for education in sub-Saharan Africa - Adam, Taskeen; El-Serafy, Yomna; Podea, Marius; Haßler, Björn (EdTech Hub, 2021)
We set out to investigate the existing and potential use cases of open-source, modular ‘building blocks’ to build digital platforms for education in sub-Saharan Africa (SSA). Building blocks fall into two main categories: teaching and learning (e.g., learning management systems) and education system management (e.g., data collection tools).
10.5281/zenodo.4913283 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0048 10.53832/edtechhub.0049 2339240:487NSL2N 2339240:96WXZFG3 2339240:BXUFCQ98 2339240:QUJFSUDE 2405685:4NFT3P7H 2405685:MZSKKWUZ 2405685:NVIUXYC6 2405685:PIXT9J66 2405685:RL5CTZU3 2405685:U8GMZZ48 2486141:7MQA6V3G 4656463:6378IJC5 4656463:TD3MYCHJ
Keywords: _EdTechHub_Output; _MELA_seen

STEM: breaking gender stereotypes - UNGEI (UNGEI, 2021)
In some Western cultures, pink is for girls, blue is for boys. Why? It just is. You might hear mothers remark with wonder that their little girls just love the pink dress (that was given to them). You may have heard fathers insist that their sons not wear pink clothing. It’s interesting to think that at the end of the nineteenth century in the USA, pink was actually the colour preferred for boys, it being a softer version of military red. Things change. The accepted wisdom that stereotypes originally come from a place of truth is erroneous. No credible research has indicated that girls gravitate to pink things without any cultural prompting. Our gendered behaviour is primarily socially conditioned. Research suggests that the idea of a female brain and a male brain is false [1]. Rather, the plasticity of the brain means that it can be moulded – from birth onwards – through learning, engaging in the world and being socially conditioned. This includes learning and absorbing gender stereotyping. Gendered colours are harmless though, right? No, not really. Any gender stereotype will reinforce a gender bias. In 2019, a Fawcett Society study found that 45 per cent of people said that when they were children, they experienced gender stereotyping as they were expected to behave in a certain way [2]. Seven in 10 younger women (18-34s) affected by stereotypes say their career choices were restricted [3]. Around 70 per cent of individuals in 34 countries associated science with males more than with females [4]. © UNICEF/UN0364176/XimendazCaregivers and teachers often reproduce the stereotype that boys are better in science and mathematics than girls, encouraging girls to aspire to ‘female-oriented’ careers instead of ‘male’ STEM related ones [5,6]. To compound this negative reinforcement, curriculum and learning materials reinforce gender stereotypes and unequal gender norms in STEM. In India, illustrations in math and science textbooks in primary school show 6 per cent girls, but more than 50 per cent boys [7]. The stereotyping sanctioned by parents, teachers and the curriculum itself negatively impacts a girl’s self-belief – and her future aspirations [8]. When three women won the Nobel Prize for science in 2020, it was newsworthy partly because not many women have won the prize over the years. But is it also newsworthy because, even today, many would not expect women to be such high achievers in science, technology, engineering and mathematics. Engineering is for boys. Mechanical toys are for boys. Science experiments are for boys. These are the stereotypes we learn. Where does this thinking come from? There’s obviously a lot to unpack here: traditional roles in society born out of a female’s capability to bear children, or stronger upper body strength, on average, amongst males, for example. But they don’t speak to our cognitive and intellectual potential. And I’m sure there would be many who would dispute every particular of the above. Questioning norms that are the foundation of our interaction with the world is difficult for all of us to do. © UNICEF/UN0145559/SchermbruckerAcknowledging that stereotypes exist is straightforward. Deciding that they shouldn’t constrain our behaviour and life path is a little harder. But confronting and actively challenging these stereotypes – indeed, breaking them! – is an altogether more difficult process. How do we do it? How do we take organic and grassroots solutions toward a tipping point of change? This International Girls in ICT Day (22nd April), UNGEI hosted an Instagram Live event to explore these important questions. Transform Education members Maryam and Nivaal and NASA engineer Farah Alibay talked about working with NASA on the Mars 2020 mission, how to drive progress for gender equality in STEM and why representation matters. Shifting power in STEM starts with listening to the experts and girls themselves, such as the inspiring changemakers on UNICEF’s Teen. Girl. Activist site. Debunking stereotypes is in their very capable hands… The first thing we need to do is recognize that there is a societal bias... let’s recognize that we are treating girls differently and that they are not being given the same opportunities. Now that we’ve started to recognize that problem, I think...normalizing STEM for girls, providing resources, and providing a safe space for girls is really important. Farah Alibay, Systems Engineer, NASA (UNGEI International Girls in ICT IG Live Event) Some choose to tackle stereotypes head-on, like the ‘Talent Viewer’ in the Netherlands, to break the stereotype that girls can’t successfully engage in STEM. Girls and boys in primary school (aged 9 to 12) assign talents to each other, discuss them, then investigate what STEM professions used these talents. This looks at certain talents being appropriate for STEM, not gender. A woman working in a STEM field talks to the classes about her job, effectively role modelling for girls. Critically, parents are encouraged to discuss the talents with their child and teachers participate in professional development on gender awareness, STEM education and talent development. The evaluation of the programme has indicated a positive change in attitude in both girls and boys towards girls’ participation in STEM. Around 46,000 children have engaged in this exciting work to date. © UNICEF/UNI363793/AryanAnother approach is simply to place girls in STEM-related industries, to show that it’s a natural place for both men and women, like the ‘Technogirls’ programme. This is a public-private partnership in South Africa that seeks to enhance the career uptake by disadvantaged girls in STEM fields (which is critical to the country’s economic growth). It identifies school-going young women from disadvantaged communities and places them in corporate mentorship and job-shadowing programmes. So far, 11,241 girls have engaged in structured job-shadowing programmes – and 78 per cent of them who have gone on to study in one of three scarce skills STEM fields in the country. These women become role models for the next generation and many of them are now mentors to new intakes of girls. The best investment is...girls' quality STEM education. And if we can give support to girls for quality STEM education, they will pay back successfully in the future to make a better world. Nasrin Siddiqa, Brookings Echidna Global Scholar (UNGEI@20 Forum) Other education systems have worked on how they teach STEM to ensure that girls aren’t overlooked or left behind. UNICEF in Ghana has worked with the Korea International Cooperation Agency and the Ghana Education Service on the ‘Better Life for Girls’ project. Focused on dismantling gender norms, the project included gender-responsive pedagogy (teaching and learning processes that pay attention to the specific learning needs of girls and boys) in mathematics and science, and providing life skills and leadership training for adolescent girls – helping more than 4,000 girls to stay in school and explore their potential. Training teachers on gender-responsive pedagogy helped to change girls’ perceptions of their own abilities – and this has a knock-on effect in the learning they pursue. If girls had believed the stereotype about not being good at mathematics, what other stereotypes can they challenge? And that is surely a question for all of us. During UNGEI’s 20th Anniversary Forum (UNGEI@20), activists, experts and leaders came together to explore what it will take to close the STEM gender gap in education and thus help girls fulfil their leadership potential. The event concluded that we need a gender-transformative approach to education, increasing opportunities for girls to develop digital skills and building their confidence and aspirations to pursue careers as STEM professionals. Technology is such a useful tool because it doesn't just provide mentors. It provides resources. It provides community. When you take away that access to tech, you take away that access to education as well, that basic human right. Audrey Pe, WiTech Founder (UNGEI@20 Forum) In the pursuit of equity in digital literacy and STEM skills, especially as we look toward a world of work where 9 in 10 jobs will require digital skills, UNICEF is proud to mobilize commitments alongside other public and private partners as an Action Coalition for Technology and Innovation as part of the Generation Equality Forum. These commitments include advancing girl-designed solutions to learning fit for a digital world, and advancing an outcome fund for digital literacy equity that brings together the best of public and private human and financial resources. © UNICEF/UNI363793/AryanIn the context of the Covid-19 crisis, which exposed structural inequalities in education and access to technology, these types of interventions are more important than ever. If we are to deliver on our global commitments to Sustainable Development Goals (SDGs) 4 and 5, we need to understand just how much harm stereotypes of any kind can be, particularly to young, vulnerable, curious children. If we are serious about helping children to achieve their potential – for their own development and so they can contribute to their communities and the world – then we need to minimize the forces that limit that potential. This includes gender stereotyping. We need to start celebrating children for who they are, not who we think they should be, based on a pointless stereotype. Let’s help them to access their rights to be themselves. Let’s help them to wear whatever colour they like.
KerkoCite.ItemAlsoKnownAs: 2339240:RFBQ67SV 2405685:PWYK67HD